Longitudinal Analysis of Group A Streptococcus emm Types and emm Clusters in a High-Prevalence Setting: Relationship between Past and Future Infections. (21st November 2019) - Campbell, Patricia Therese; Tong, Steven Y C; Geard, Nicholas; Davies, Mark R; Worthing, Kate A; Lacey, Jake A; Smeesters, Pierre R; Batzloff, Michael R; Kado, Joseph; Jenney, Adam W J; Mcvernon, Jodie; Steer, Andrew C
Abstract: Group A Streptococcus is a pathogen of global importance, but despite the ubiquity of group A Streptococcus infections, the relationship between infection, colonization, and immunity is still not completely understood. The M protein, encoded by the emm gene, is a major virulence factor and vaccine candidate and forms the basis of a number of classification systems. Longitudinal patterns of emm types collected from 457 Fijian schoolchildren over a 10-month period were analyzed. No evidence of tissue tropism was observed, and there was no apparent selective pressure or constraint of emm types. Patterns of emm type acquisition suggest limited, if any, modification of future infection based on infection history. Where impetigo is the dominant mode of transmission, circulating emm types either may not be constrained by ecological niches or population immunity to the M protein, or they may require several infections over a longer period of time to induce such immunity. Abstract : We examined longitudinal patterns of emm types in group A Streptococcus samples collected from Fijian schoolchildren. In a setting where impetigo is the dominant mode of transmission, we found no evidence that infection history modifies future infection.